2017
DOI: 10.4103/ijpvm.ijpvm_63_16
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Iranian version of pregnancy related anxiety questionnaire

Abstract: Background:Pregnancy is an acute period in the lifetime of women, during which numerous excitatory physical and social changes occur. The purpose of this study is confirmatory factor analysis of Pregnancy Related Anxiety Questionnaire (PRAQ) that is designed in Iranian pregnant women population.Methods:A total of 170 pregnant women in health centers of Kerman city were chosen through random sampling method and completed PRAQ questionnaire and Beck Anxiety Inventory (BAI). In this study, confirmatory factor ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 22 publications
0
26
0
Order By: Relevance
“…In the present study, data were collected using demographic and obstetric questionnaires, the Wijma Delivery Expectancy/Experience Questionnaire (W-DEQ) -Version A, the Pregnancy-Related Anxiety Questionnaire (PRAQ) by Van den Bergh, and the Edinburgh Perinatal Depression Scale (EPDS). The Persian version of all instruments used in this study have been validated in Iran after obtaining license from the copyright holders of the English version of the tools [12][13][14].…”
Section: Data Collection Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, data were collected using demographic and obstetric questionnaires, the Wijma Delivery Expectancy/Experience Questionnaire (W-DEQ) -Version A, the Pregnancy-Related Anxiety Questionnaire (PRAQ) by Van den Bergh, and the Edinburgh Perinatal Depression Scale (EPDS). The Persian version of all instruments used in this study have been validated in Iran after obtaining license from the copyright holders of the English version of the tools [12][13][14].…”
Section: Data Collection Toolsmentioning
confidence: 99%
“…They reported the reliability of the 'fear of giving birth', 'worries about bearing a physically or mentally handicapped child', and 'concern about own appearance' subscales with scores of 0.83, 0.87, and 0.83, respectively [17]. In Iran, the psychometric assessment of this questionnaire was carried out by Karamouzian et al, and its reliability was reported as 0.78 [13]. In the present study, the reliability of this questionnaire was confirmed with a Cronbach's alpha of 0.82.…”
Section: Data Collection Toolsmentioning
confidence: 99%
“…Studies have shown that this questionnaire has high reliability and validity. Its internal consistency coefficient has been reported as 0.92, while its test-retest reliability with a one-week interval was 0.75, and the correlation of its items ranges from 0.30 to 0.70 (Askarizadeh, Karamoozian, & Darekordi, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, each question is graded between 1.0 and 7.0, while the total score range of pregnancy anxiety was between 17 and 119. [ 24 ]…”
Section: Methodsmentioning
confidence: 99%